PERAN PENTING PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR - Umi Musya’adah (Aulada : Jurnal Pendidikan dan Perkembangan Anak, 2020)
Education could be an important aspect in a statedevelopmentand building student character especially. Religion education was hoped to facilitate elementary school students developing their faith since early, with the result they don’t only know and understand the value until they can live in peace and tolerant with other religion embracers. Later, islam religion is not only a most embracer religion in the world but can be rahmatan lil alamien religion.